2011
DOI: 10.1002/pts.942
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Paperboard Structure and Processing Conditions on Forming of Complex Paperboard Structures

Abstract: Experiments were made with a laboratory apparatus for forming paper sheets into double-curved structures. The purpose was to learn more about the design criteria for forming of paper materials into complex shapes. The influence of forming parameters such as moisture and temperature was studied, and the performance of some common pulps as raw materials for the paper sheets was evaluated. Papers made from short hardwood fibres performed worse than papers from other pulps, and the method of moisture application w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 3 publications
2
28
0
Order By: Relevance
“…In a few publications the process‐dependent material elongation for press forming and hydroforming is mentioned as a side effect. In press forming, the investigations focus on the relationships between the process parameters with respect to the deformation and damage mechanisms as well as the sealing of the produced trays.…”
Section: Introductionmentioning
confidence: 99%
“…In a few publications the process‐dependent material elongation for press forming and hydroforming is mentioned as a side effect. In press forming, the investigations focus on the relationships between the process parameters with respect to the deformation and damage mechanisms as well as the sealing of the produced trays.…”
Section: Introductionmentioning
confidence: 99%
“…In principle, elongation is the ability of material to increase its linear length under the action of external mechanical forces; the increase in the linear length is attributed to elastic and plastic deformations (Levlin and Söderhjelm 1999). This property increases the tensile energy absorption (TEA) potential of paper, which is defined as the integral of the tensile force and specimen elongation up to the point of failure, and is important for runnability of the web on the paper machine and in the printing house (Hristopulos and Uesaka 2002;Uesaka 2005;Deng et al 2007), and for converting operations of paper and paperboard (Gärd 2002;Post et al 2011;Östlund et al 2011). Elongation of paper is also one of the central components of formability of paper-based materials (Vishtal and Retulainen 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The hydroforming process consists of multiple parameters, which can be difficult to control individually, thus making the experimental determination of the quantitative effects of each parameter on the hydroforming process difficult (although some general effects of the parameters have been identified empirically in the experimental hydroforming studies by Östlund et al . Östlund et al and Groche et al .). Groche et al A finite element method (FEM) approach is beneficial, because FEM analysis would allow one to study the effects of each individual parameter on hydroforming and to optimize the hydroforming process for paper materials.…”
Section: Introductionmentioning
confidence: 95%
“…The hydroforming process for paper materials was introduced simultaneously in two separate research groups: the experimental study conducted by Östlund et al Östlund et al identified many of the important process parameters for hydroforming, and the experimental and numerical study by Groche et al . Groche et al identified friction as an important process parameter.…”
Section: Introductionmentioning
confidence: 99%